Effectiveness of Extract Binahong Leaves (Anredera cordifolia) as Natural Vaccines on Blood Profile of Broiler Chicken - Wulansari, Asri; Mayasari, Novi; Firmansyah, Indra; Ismiraj, Muhammad Rifqi (Bulletin of Applied Animal Research, 2024)
This study investigates the efficacy of binahong (Anredera cordifolia) leaf extract as a natural alternative to synthetic vaccines on the blood profile of broiler chickens. One hundred COBB broilers were divided into five treatment groups with four replications each: P0 (standard ND vaccine), P1 (no treatment/control), P2 (binahong leaf extract 0.25 g/ml), P3 (binahong leaf extract 0.15 g/ml) and P4 (binahong leaf extract 0.05 g/ml). Blood samples were collected and analyzed after 28 days to assess hemoglobin (Hb), packed cell volume (PCV), and erythrocyte levels. Data were statistically analyzed using one-way ANOVA and Duncan’s post-hoc test. Results showed that binahong leaf extract significantly increased hemoglobin and erythrocyte levels, with the highest Hb observed at 7.74 g/dl in the 0.25 g/ml group and the highest erythrocyte count at 2.84 x 106 cells/mm3 in the 0.15 g/ml group. Although PCV levels were highest in the 0.25 g/ml group, differences across treatments were not statistically significant. These findings suggest that binahong leaf extract, particularly at higher concentrations, may improve blood parameters in broilers, suggesting its potential as a natural health promoter in poultry production. Keywords: broiler chickens, binahong leaf extract, blood profile, natural vaccine